2016
DOI: 10.1155/2016/2074970
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Carcinoid and Concurrent Carcinoid Syndrome in an Adolescent Female

Abstract: Endobronchial carcinoid tumors are the most common intrabronchial tumors in children and adolescents. Common signs and symptoms include persistent cough and wheezing not responsive to bronchodilators, hemoptysis, and recurrent fever. Diagnosis is frequently made by imaging and direct visualization with flexible bronchoscopy; surgery remains the gold standard treatment, and lung-sparing resections should be performed whenever possible. Though carcinoid syndrome—characterized by flushing, palpitations, wheezing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Bronchial carcinoid is usually detected as a mass on chest imaging performed for respiratory symptoms. 16,19 Typical carcinoids tend to be more centrally located, whereas atypical carcinoids tend to be located peripherally. Diagnosis is generally confirmed by histopathological examination following endobronchial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial carcinoid is usually detected as a mass on chest imaging performed for respiratory symptoms. 16,19 Typical carcinoids tend to be more centrally located, whereas atypical carcinoids tend to be located peripherally. Diagnosis is generally confirmed by histopathological examination following endobronchial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In these refractory patients, increasingly, either more frequent dosing of the somatostatin analogue is used or high-dosing at the same time interval to control the extra-cardiac symptoms, and this approach is frequently effective(up to 80%)[••3,711,26,29,50,•146]. Recent studies also support the conclusion that pasireotide(SOM230), a somatostatin analogue with high affinity for somatostatin receptor subtypes-sst1,2,3,5 [in contrast to octreotide/lanreotide with high affinity for sst2,5], may be effective in controlling noncardiac symptoms(diarrhea/flushing) in a proportion of octreotide/lanreotide resistant patients with carcinoid symptoms[12,37,147]. In one phase II study[12] in 48 patients with carcinoid-syndrome no longer responsive to octreotide LAR, pasireotide controlled the diarrhea/flushing in 27% of the patients.…”
Section: Carcinoid-syndrome: Advances Recent Insights Controversiesmentioning
confidence: 96%
“…In one phase II study[12] in 48 patients with carcinoid-syndrome no longer responsive to octreotide LAR, pasireotide controlled the diarrhea/flushing in 27% of the patients. With pasireotide treatment hyperglycemia developed in higher proportion of patients than seen with octreotide-LAR[145] with hyperglycemia in 28%,16% and 79% in three different studies[12,37,147]. In a study investigating the possible mechanism of the pasireotide induced hyperglycemia in normal volunteers, it was found that pasireotide decreased the incretin response and insulin secretion without affecting peripheral or hepatic insulin sensitivity[148].…”
Section: Carcinoid-syndrome: Advances Recent Insights Controversiesmentioning
confidence: 99%
“…The long-term results of persistently elevated hormone levels include telangiectasias of veins, valvular heart disease (right side more commonly involved), and retroperitoneum fibrosis. Flushing of the skin can be prolonged in the setting of carcinoid syndrome due to lung NET and it occurs more in the upper anterior part of the body [61,62].…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…Excision of the tumour is the best treatment [67]. Unlike other organ NETs (even with significant liver metastasis), carcinoid crisis risk with lung NETs is low, and hence prophylactic administration of octreotide before any tumour manipulation (biopsy or resection) is not recommended [62]. But still, when handling such tumours, clinicians should be aware of the possibility of the carcinoid crisis and the benefit of octreotide in such a scenario.…”
Section: Treatmentmentioning
confidence: 99%